2006
DOI: 10.2337/dc05-2425
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Foot Infections in Individuals With Diabetes

Abstract: OBJECTIVE -To prospectively determine risk factors for foot infection in a cohort of people with diabetes.RESEARCH DESIGN AND METHODS -We evaluated then followed 1,666 consecutive diabetic patients enrolled in a managed care-based outpatient clinic in a 2-year longitudinal outcomes study. At enrollment, patients underwent a standardized general medical examination and detailed foot assessment and were educated about proper foot care. They were then rescreened at scheduled intervals and also seen promptly if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
429
2
26

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(468 citation statements)
references
References 55 publications
11
429
2
26
Order By: Relevance
“…23 In diabetics, local infections, with plantar ulcers, edema, and hyperemia, are known high-risk factors for amputations. 8,24 However, the present study observed that only sepsis was related to major amputations, irrespective of the presence of local infection. In these cases, the importance of taking a treatment decision immediately to prevent progression to septic shock and death cannot be overstated.…”
Section: 15contrasting
confidence: 44%
See 1 more Smart Citation
“…23 In diabetics, local infections, with plantar ulcers, edema, and hyperemia, are known high-risk factors for amputations. 8,24 However, the present study observed that only sepsis was related to major amputations, irrespective of the presence of local infection. In these cases, the importance of taking a treatment decision immediately to prevent progression to septic shock and death cannot be overstated.…”
Section: 15contrasting
confidence: 44%
“…Diabetic patients with neuropathy and/or ischemia are more susceptible to ulceration and infection, which generally results in amputation. 8 Traumatisms and malignant tumors are responsible for, respectively, 10.6% and 5.8% of lower limb amputations. 2 Despite the increase in the number of revascularization interventions, some studies indicate that the prevalence of amputations has remained unaltered because of the increase in cases of atherosclerosis and diabetes mellitus and aging of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of the bone is a common complication of foot ulceration in patients with diabetes and presents a considerable therapeutic challenge [1]. Despite the existence of published guidelines [2,3], approaches to the management of osteomyelitis of the foot in diabetic patients may vary quite widely, especially as few robust data are available to inform clinical practice [4].…”
Section: Introductionmentioning
confidence: 99%
“…16 It is possible that this fact is related to the wide range of factors that act synergistically together in establishment and proliferation of lesions of the diabetic foot. 5 Bacterial resistance was observed for several different drugs, but it was clindamycin, which is widely utilized in empirical regimes for treatment of the diabetic foot, to which bacteria were most often resistant (59%). It should be pointed out that, in this study, anaerobic germs, which tend to be treated using clindamycin, were not investigated.…”
Section: 2814mentioning
confidence: 99%
“…3 Efforts should be concentrated on achieving early diagnosis of infection of diabetic ulcers, because infection is associated with up to 56 times greater risk of hospital admissions and up to 155 times the risk of amputation. 4,5 In addition to the suffering inflicted on patients, hospital treatment of the diabetic foot tends to be of high cost to the healthcare system. Even after hospital discharge, these patients generally require permanent care and, sometimes, repeated admissions to treat the same problem.…”
Section: Introductionmentioning
confidence: 99%